A study of shoulder rest's feet height variation on upper trapezius muscle activity in violinists - Wong, S. F.; Lei, I. P. (2015 IEEE International Conference on Industrial Engineering and Engineering Management (IEEM), 2015)
Violin is an important role in music history. Comfort of holding violin also becomes a concern since this affects the ability and quality of performance. Literature review pointed out that upper trapezius is the related muscle when playing violin and proved that the performance of playing with a shoulder rest is greater than without it. However, the height of shoulder rest's two feet was only stated that all ‘high’ is better then all ‘low’, none of any researches study the different combination of height variation of the two feet. In this study, eight subjects were invited to participate the experiment and twelve shoulder rests were provided to test by applying human factors. Surface electromyography was used to collect the left and right upper trapezius muscle activities. The results showed there were significant differences and it indicated that the variation height of shoulder rest's feet could affect the upper trapezius.